The ban in Mari and in the Bible - Malamat, Abraham (1966)
The Mari documents have had considerable impact on the study of the early history of the Israelites and have brought about a clearer understanding of the social and religious practices and institutions, especially in their nomadic ""pre-history"" and in the period of the settlement. One most instructive parallel manifestation between Mari and Israel is seemingly the concept of the ""ban"" and its enforcement as punishment for transgression.
Keywords: Mari documents; Early history of the Israelites